PERCEIVED STIGMA, ATTITUDINAL AND INSTRUMENTAL BARRIERS TO MENTAL HEALTH HELPSEEKING BEHAVIOUR AMONG CAMEROONIAN REFUGEES IN TAKUM LGA, TARABA STATE, NIGERIA - Micah, Terah Barde; Ruwan, Felix I.I.; Ukeh, Moses Ichongo (African Journal of Social and Behavioural Sciences, 2024)
As of mid of year 2022, UNHCR had registered about 77,000 Cameroonian men, women, and children as refugees in the states of Akwa-Ibom, Anambra, Benue, Cross River, Enugu, and Taraba. There is a growing concern that a considerable number of Cameroonian refugees in Taraba State faces barriers with regards to seeking mental health support and care. It is in this stand that this study examined the perceived barriers to mental health help-seeking behaviour among Cameroonian refugees in Takum LGA, Taraba State, Nigeria. Using a quantitative design, a cross-sectional survey was employed and 312 (43.6% males and 56.4 females) Cameroonian refugees were sampled through a snowball sampling technique. The data were collected using the Barriers to Access to Care Evaluation (BACE v3), and three hypotheses were tested using the chi-square test (goodness of fit). The results revealed that Cameroonian refugees residing in Takum, Taraba State, Nigeria, had significantly greater levels of perceived stigma as a barrier to mental health help-seeking behaviour (χ2 = 10.051, p <.05). Similarly, the results indicated significantly greater levels of perceived attitudinal barriers to mental health help-seeking behaviour (χ2 = 23.705, p <.05). Finally, the results revealed significantly greater levels of instrumental barriers to mental health help-seeking behaviour (χ2 = 6.782, p <.05). The findings indicate that Cameroonian refugees in Takum, Taraba State, Nigeria, face significant perceived stigma, attitudinal, and instrumental barriers to seeking mental health help. The study recommended that mental health professionals, policymakers and stakeholders should prioritize the mental well-being of refugees during programming, policy making/decision, and implementation of services.